2017
DOI: 10.14740/jcs316w
|View full text |Cite
|
Sign up to set email alerts
|

The Value of C-Reactive Protein in Enhancing Diagnosis of Acute Appendicitis

Abstract: Background: Acute appendicitis is one of the most common surgical emergencies. Accurate diagnosis of acute appendicitis is based on careful history, physical examination, laboratory and imaging findings. The aim of this study was to analyze the role of C-reactive protein (CRP) in improving the accuracy of diagnosis of acute appendicitis and to compare it with the histopathology findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…2014), in which more number of CRP positive patients were females as compared to males. [6,7,8,9] It has been reported by the previous studies that age group most effectively affected with inflammatory diseases was 40- [8, 10,11] In the present study the CRP titre 48mg/L was obtained in maximum number of patients. The study showed similar results which are comparable to the studies reported by [7,11,12] The findings of this study that most patients with rheumatoid arthritis showed highly raised titres of serum CRP were similar to the study reported by Shrivastava et al(2013) and Andveera et al(2014).…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…2014), in which more number of CRP positive patients were females as compared to males. [6,7,8,9] It has been reported by the previous studies that age group most effectively affected with inflammatory diseases was 40- [8, 10,11] In the present study the CRP titre 48mg/L was obtained in maximum number of patients. The study showed similar results which are comparable to the studies reported by [7,11,12] The findings of this study that most patients with rheumatoid arthritis showed highly raised titres of serum CRP were similar to the study reported by Shrivastava et al(2013) and Andveera et al(2014).…”
Section: Resultssupporting
confidence: 47%
“…[6,7,8,9] It has been reported by the previous studies that age group most effectively affected with inflammatory diseases was 40- [8, 10,11] In the present study the CRP titre 48mg/L was obtained in maximum number of patients. The study showed similar results which are comparable to the studies reported by [7,11,12] The findings of this study that most patients with rheumatoid arthritis showed highly raised titres of serum CRP were similar to the study reported by Shrivastava et al(2013) and Andveera et al(2014). [8,9] However, results of present study vary from other studies - [6,7,13] In the present study raised CRP levels obtained in 76% patients with chronic inflammatory diseases and 24% patients with acute inflammatory diseases.…”
Section: Resultsmentioning
confidence: 50%
“…The utility of CRP in diagnosing appendicitis has been evaluated in many studies. Negative CRP levels would most likely be associated with normal appendix [ 7 ]. In contrary, Amalesh T et al showed that the sensitivity, specificity, PPV, and NPV for CRP in appendicitis was 91%, 42%, 88%, and 48%, respectively, and that it may not be a useful tool to surgeons [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6] Pada kelompok pasien yang hanya terdiri dari pasien dengan apendisitis terkomplikasi, CRP menunjukkan sensitivitas sebesar 97%, tetapi ketika digabungkan dengan kelompok apendisitis akut tanpa komplikasi, sensitivitas turun menjadi 66%. [18] Tabel 1. AUC Berbagai Biomarker Potensial pada Apendisitis Komplikasi [16] CRP diproduksi di dalam hepar sehingga tidak menggambarkan inflamasi yang terjadi pada apendiks maupun peritoneum.…”
Section: Ekspresi Mmp Pada Serumunclassified
“…[6,20] Tabel 2. Sensitivitas Pemeriksaan pada Apendisitis Akut [17,18,20] No Meto de [19] MMP-9 merupakan biomarker paling utama yang dapat dideteksi pada apendisitis perforasi. MMP-9 selalu dijumpai mengalami peningkatan yang signifikan pada pemeriksaan histopatologi, biopsi cairan pada area perforasi, pemeriksaan serum, dan cairan peritoneum.…”
Section: Ekspresi Mmp Pada Serumunclassified